Current Insights on the Impact of Gamma-Hydroxybutyrate (GHB) Abuse - Tay E; Lo WKW; Murnion B (Dove Medical Press, 2022)
Emma Tay,1 Wing Kwan Winky Lo,2 Bridin Murnion3 1Drug Health Services, Western Sydney Local Health District, Sydney, NSW, Australia; 2Faculty of Medicine, University of New South Wales, Sydney, NSW, Australia; 3Faculty of Medicine and Health, University of Sydney, Sydney, NSW, AustraliaCorrespondence: Bridin MurnionDrug Health Services, Western Sydney Local Health District, 4A Fleet Street, North Parramatta, NSW, 2151, Australia, Tel +61 2 9840 3888, Fax +61 2 9840 3927, Email bridin.murnion@sydney.edu.auAbstract: Recreational gamma-hydroxybutyrate (GHB) use, although less common than other substance use, is increasingly recognised and is over-represented in emergency toxicology presentations. This narrative review summarizes GHB pharmacology, current patterns of use, potential harms and management of GHB toxicity and withdrawal. There is a complex interplay between GHB and GABA as GHB is both a prodrug and metabolite of GABA and GHB activates both GHB and GABA receptors. GHB is rapidly absorbed, with effects seen within minutes of ingestion. Metabolism is non-linear at higher doses. While GHB is listed as a controlled substance, its precursor's gamma-butyrolactone (GBL) and 1,4-butanediol (1,4-BD) are easily available as both have industrial applications. National surveys indicate low rates of GHB use, with identification of high-risk populations in men who have sex with men and polysubstance users. GHB is one of the three drugs most commonly used in chemsex. GHB is often co-ingested with other interacting psychoactive substances. Acute toxicity is dose-dependent, and management is supportive care. Withdrawal management is generally with benzodiazepines with addition of baclofen for more severe withdrawal. Barbiturates may have a role. Titration and tapering of pharmaceutical GHB is commonly used in the Netherlands. Complicated withdrawal with delirium may require intensive care and treatment with intravenous sedation. There are high rates of relapse after withdrawal and medications for longer-term management are currently being investigated. Chronic use is associated with poorer mental, physical and sexual health, social dysfunction and poor work performance. Laboratory detection is complicated as GHB is an endogenous substance with a short half-life, and therefore not often routinely assayed in the clinical setting. Future research should focus on improving GHB detection and management of GHB withdrawal and dependence. Interventions specific for high-risk groups should be developed and assessed.Keywords: gamma-hydroxybutyrate, gamma-butyrolactone, 1, 4-butanediol, use, harms, management